MODELING AND INVESTIGATION OF NOISE IMMUNITY REED-SOLOMON CODE TO PROVIDE INCREASED IMMUNITY IN DVB-T2 STANDARD DIGITAL TELEVISION SYSTEM - A. A. Yarmukhamedov, A.B. Jabborov. (Journals Park Publishing, 2023)
In this paper, the noise-correcting Reed-Solomon code is investigated and modeled to provide an increase in noise immunity in a digital television system of the DVB-T2 standard. Theoretical and practical algorithm of functioning of the Reed-Solomon noise-correcting codec has been studied. The error-correcting Reed-Solomon code in the DVB-T2 standard digital television system with the developed interactive computer simulation program in the Matlab/Simulink programming language, the dependence of the number of errors on the error probability for the noise-correcting Reed-Solomon code is modeled and investigated.
Keywords: Reed-Solomon code, error-correcting code, DVB-T2 standard, encoder and decoder, noise immunity, interference, noise, error probability, syndrome, code word length.